Effects of a magnetic field on double-diffusive convection of a nanofluid in a cavity saturated by wavy layers of porous media: ISPH analysis - Aly, Abdelraheem M.; Alsedais, Noura; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2022)
Purpose The purpose of this study is to use the incompressible smoothed particle hydrodynamics method to examine the influences of a magnetic field on the double-diffusive convection caused by a rotating circular cylinder with paddles within a square cavity filled by a nanofluid. Design/methodology/approach The cavity is saturated by two wavy layers of non-Darcy porous media with a variable amplitude parameter. The embedded circular cylinder with paddles carrying T_h and C_h is rotating around the cavity center by a uniform circular velocity. Findings The lineaments of nanofluid velocity and convective flow, as well as the mean of Nusselt and Sherwood numbers, are represented below the variations on the frequency parameter, amplitude parameter of the wavy porous layers, Darcy parameter, nanoparticles parameter, Hartmann number and Ryleigh number. The performed simulations showed the role of paddles mounted on circular cylinders for enhancing the transmission of heat and mass within a cavity. The wavy porous layers at the lower Darcy parameter are playing as a blockage for the nanofluid flow within the porous area. Increasing the concentration of the nanoparticles to 6% reduces the maximum flow speed by 8.97% and maximum streamlines |psi|(max) by 10.76%. Increasing Hartmann number to 100 reduces the maximum flow speed by 65.83% and |psi|(max) by 75.54%. Originality/value The novelty of this work is to examine the effects of an inclined magnetic field and rotating novel shape of a circular cylinder with paddles on the transmission of heat/mass in the interior of a nanofluid-filled cavity saturated by undulating porous medium layers.
Keywords: ISPH; Double-diffusive; Paddles; Rotating cylinder; Wavy porous layers